Global Digital Cultures: Perspectives from South Asia - Punathambekar, Aswin (University of Michigan Press, 2019)
Digital media histories are part of a global network, and South Asia is a key nexus in shaping the trajectory of digital media in the twenty-first century. Digital platforms like Facebook, WhatsApp, and others are deeply embedded in the daily lives of millions of people around the world, shaping how people engage with others as kin, as citizens, and as consumers. Moving away from Anglo-American and strictly national frameworks, the essays in this book explore the intersections of local, national, regional, and global forces that shape contemporary digital culture(s) in regions like South Asia: the rise of digital and mobile media technologies, the ongoing transformation of established media industries, and emergent forms of digital media practice and use that are reconfiguring sociocultural, political, and economic terrains across the Indian subcontinent. From massive state-driven digital identity projects and YouTube censorship to Tinder and dating culture, from Twitter and primetime television to Facebook and political rumors, Global Digital Cultures focuses on enduring concerns of representation, identity, and power while grappling with algorithmic curation and data-driven processes of production, circulation, and consumption.